Digital Worksheet Transformation for Contextual Learning : Integration of PBL, SSI, and STEM - Mentari, Mentari; Syukri, Muhammad; Halim, A; Maghfirah, Siti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to examine the needs and expectations for the development of digital student worksheets based on Problem-based Learning (PBL), Socio-scientific Issues (SSI), and Science, Technology, Engineering, Mathematics (STEM), which can enhance students' critical thinking skills. This study employed a descriptive method using mixed approachs involving 105 respondents consisting of 73.3% teachers and 26.7% students from 20 provinces in Indonesia. Data were collected through an online questionnaire, in-depth interviews, curriculum analysis, and literature review, then analyzed using triangulation to validate the findings.The results showed that the majority supported the development of flipbook-based digital worksheets, featuring keyword search, links to videos or animations, and interactive quizzes. The integration of PBL enables students to solve real-world problems, such as the impacts of smoking habits or air pollution, while the SSI approach fosters social awareness. The STEM approach provides opportunities for students to conduct experiments and generate creative solutions relevant to everyday life. This study concludes that the development of PBL-SSI-STEM-based worksheets is not only aligned with deep learning but also provides meaningful learning experiences. These worksheets are expected to help students understand abstract concepts, enhance critical thinking skills, and prepare them to face global challenges through innovative technological approaches.